32. To Proton therapy quality assurance optimization through a new phantom design. (December 2017) - Wanko, N.; Vidal, M.; Gérard, A.; Hérault, J.
Abstract : Introduction: The Antoine Lacassagne Center is equipped with the first ProteusOne® (IBA PT) which delivers a maximum energy beam of 226 MeV with the Pencil Beam Scanning technique. Nowadays, the daily dosimetric quality assurance of the machine includes uniformity, symmetry and field size checks of a 20 × 20 cm 2 field with range shifter, the range constancy for one maximum energy and absolute dose measurement on reference conditions. All these measurements are carried out with a matrix of ionization chambers (MatriXX (IBA Dosimetry GmbH)) and last about 40 min. This work presents a phantom which allows to check more dosimetric parameters every day in less time. Methods: We designed a "UnickOne" phantom in PMMA that allows daily measurements of constancy in 2 irradiations. The gantry angle is 0° and the phantom is placed on the MatriXX on the table. During the first irradiation, we check: - The beam range at different energies with two wedges of different thicknesses, thus transposing the distal measurement into a transverse measurement. - Uniformity, symmetry and field size of 2 rectangular fields. - Spot size and position at 2 different depths using a 5 spots pattern in two cubes of different thicknesses. Indirectly, a verification of the Source Axis Distance is also obtained. During the second irradiation, the central cube (10 × 10 cm 2 and a thickness 5 cm) is irradiated with a field of 8 × 8 cm 2 and the absolute dose is measured at the center of this field. The ranges of two others beam energies are measured in the wedges described above. The measurements are analyzed with Matlab software and exported as daily values. Results: Thanks to the UnickOne phantom and the MatriXX, it is possible to control in less than 20 min beam parameters that are usually only measured monthly because the usual detectors (2D Scintillator, Multi-Layer Ionization Chambers) are long and hard to position properly. The daily values extracted from the Matlab analysis are used as constancy measurements while accurate checks are still carried out monthly with dedicated detectors. Conclusions: The all-in-one phantom described in this work greatly enhances and optimizes daily control of the ProteusOne. Regarding the results obtained, this phantom will soon be used in clinical routine at the Center Antoine LACASSAGNE.